2007
DOI: 10.1007/bf03245986
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and operating conditions for cobalt cerium oxide catalysts used in the conversion of synthesis gas into light olefins

Abstract: Cobalt cerium oxides, prepared using a co-precipitation procedure, were studied as catalysts for the conversion of synthesis gas to light olefins (C 2 -C 4 ). Specifically, we studied the effect of a range of preparation variables, including the molar ratio of the [Co]/[Ce] of the precipitation solution, ageing time and calcination temperature. In addition, the effects of supports and promoters on the catalysts' activity and selectivity and a range of reaction temperatures using synthesis gas with different H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…It is generally accepted that operation condition variables such as temperature, pressure, H 2 /CO feed ratio and gas space velocity influence the product distributions in FT synthesis [23][24][25][26]. The catalyst was reduced in atmospheric pressure in a flow stream of H 2 with flow rate of 30 ml/min at 673 K for 12 h and then it was exposure the stream of H 2 + CO. 103 kinetic tests were carried out over 40%Fe 60%Ni and 5% Al 2 O 3 on the bases of total catalyst weight.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that operation condition variables such as temperature, pressure, H 2 /CO feed ratio and gas space velocity influence the product distributions in FT synthesis [23][24][25][26]. The catalyst was reduced in atmospheric pressure in a flow stream of H 2 with flow rate of 30 ml/min at 673 K for 12 h and then it was exposure the stream of H 2 + CO. 103 kinetic tests were carried out over 40%Fe 60%Ni and 5% Al 2 O 3 on the bases of total catalyst weight.…”
Section: Resultsmentioning
confidence: 99%
“…After formation of catalyst precursor, further heat treatment is required to transform the catalyst precursor into the useful catalyst shape. In our previous works (Mirzaei et al, 2007;Mirzaei et al, 2008;Mirzaei et al, 2011) we demonstrated the importance of calcination conditions with respect to the catalyst activity for the hydrogenation of CO using mixed cobalt cerium oxides catalysts. The obtained results of these investigations have shown that the changes in the calcination conditions of the precipitates obtained by co-precipitation leads to phase changes toward forms that are more thermodynamically stable.…”
Section: Effect Of Calcination Conditionsmentioning
confidence: 99%
“…The experiments were carried out in a fixed bed tubular stainless steel micro reactor; different parts of the catalyst testing set up was explained in our previous work (Mirzaei et al, 2007). The detailed characteristics of the micro fixed bed reactor are illustrated in Fig.…”
Section: Catalyst Testingmentioning
confidence: 99%
“…The preparation steps in detailed were previously explained in our previous work (Mirzaei et al, 2007).…”
Section: Catalyst Preparationmentioning
confidence: 99%